1981
DOI: 10.1002/ana.410090312
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptors are increased in brains of alcoholics

Abstract: gamma-Aminobutyric acid (GABA) receptor binding was increased in postmortem brain samples of chronic alcoholic patients compared to control patients. Numbers of binding sites were augmented in alcoholic brain, with no change in affinity. Muscarinic cholinergic and benzodiazepine receptors did not differ between controls and alcoholic brains, while a modest reduction in beta-adrenergic receptors may have been related to postmortem receptor changes. The results suggest that GABAergic mechanisms might play a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…We know from animal studies that chronic alcohol exposure differentially affects subunit expression in different brain regions (see Kumar et al 2004) and our finding of reduced sleep time would therefore be consistent with reports from animal models that chronic alcohol exposure in rat brain leads to reduced levels of the α1 subunit (Montpied et al 1991). In man, subunit changes have not been systematically investigated with post-mortem studies so far showing increased or no changes in α1 and α3 polypeptide and diazepam-sensitive (α1, α2, α3, α5) benzodiazepine receptor levels in various parts of the cortex (Tran et al 1981;Dodd et al 1992;Lewohl et al 1997Lewohl et al , 2001Mitsuyama et al 1998). It is not clear which subtype or subtypes are involved in saccadic eye movements or EEG beta-power although recent evidence suggests a role for the α2 subtype in EEG beta frequency (Edenberg et al 2004).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We know from animal studies that chronic alcohol exposure differentially affects subunit expression in different brain regions (see Kumar et al 2004) and our finding of reduced sleep time would therefore be consistent with reports from animal models that chronic alcohol exposure in rat brain leads to reduced levels of the α1 subunit (Montpied et al 1991). In man, subunit changes have not been systematically investigated with post-mortem studies so far showing increased or no changes in α1 and α3 polypeptide and diazepam-sensitive (α1, α2, α3, α5) benzodiazepine receptor levels in various parts of the cortex (Tran et al 1981;Dodd et al 1992;Lewohl et al 1997Lewohl et al , 2001Mitsuyama et al 1998). It is not clear which subtype or subtypes are involved in saccadic eye movements or EEG beta-power although recent evidence suggests a role for the α2 subtype in EEG beta frequency (Edenberg et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Human post-mortem studies using a variety of radioligands show increases, decreases or no changes in GABA-BDZ receptor levels (Tran et al 1981;Freund and Ballinger 1988;Dodd et al 1992;Korpi et al 1992). One post-mortem study revealed increased expression of α1 subunit mRNA and peptide in the superior frontal cortex of alcoholics, but no such increase was seen either in the motor cortex or in the α3 subunit mRNA and peptide (Lewohl et al 1997(Lewohl et al , 2001.…”
Section: Introductionmentioning
confidence: 95%
“…Both ethanol administration (Borg et al, 1982) and alcohol withdrawal (Hawley et al, 1981) are known to increase central norepinephrine turnover, and excessive alcohol use is associated with noradrenergic toxicity (Tran et al, 1981). The strengths of this study include the timing of the testing at 1 to 4 months postdetoxification, beyond the time of normalization of acute changes in the noradrenergic system (Balldin et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…There have not been previous reports of brain benzodiazepine receptor binding studies in animal models of chronic hepatic encephalopathy. However, brain benzodiazepine receptor density and affinity were unaltered in patients with hepatic encephalopathy complicating alcoholic cirrhosis (27).…”
Section: Discussionmentioning
confidence: 99%